2017
DOI: 10.2116/analsci.33.665
|View full text |Cite
|
Sign up to set email alerts
|

UPLC-MS/MS Analysis of Methotrexate in Human Plasma and Comparison with the Fluorescence Polarization Immunoassay

Abstract: Methotrexate (MTX) plasma concentration is routinely monitored to guide the dosage regimen of rescue drugs. This study aims to develop and validate an ultra-performance liquid chromatography tandem mass spectrometry (UPLC-MS/ MS) method for plasma MTX analysis, and to establish its agreement with the fluorescence polarization immunoassay (FPIA) in patients with high-dose MTX therapy. Separation was achieved by gradient elution with methanol and water (0.05% formic acid) at 40 C with a run time of 3 min. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Concentrations of MTX in rat plasma, lymph node, and various tissues were determined by the UPLC-MS/MS method with modification of the previously reported MTX assay [53,54]. Some conditions such as mobile phase composition and sample preparation procedure were optimized for our system.…”
Section: Resultsmentioning
confidence: 99%
“…Concentrations of MTX in rat plasma, lymph node, and various tissues were determined by the UPLC-MS/MS method with modification of the previously reported MTX assay [53,54]. Some conditions such as mobile phase composition and sample preparation procedure were optimized for our system.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, it was very valuable to develop a selective, sensitive, rapid and simple method to determine the MTX concentration in children's plasma. There were several analytical methods for the determination of MTX plasma including fluorescence polarization immunoassay, 15,16 HPLC, 17 and LC-MS/MS. 18 To some extent, these previous methods were not going to deal with emergency situations (an abnormally high concentration of MTX plasma and large sample size measurement) the reason why these existed had their own drawbacks, including time-consuming requirement for plasma sample preparation, long-term chromatographic run, and low sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…For LC-MS/MS development, the extraction and purification of analytes were most challenging and it was reported that approximately 61% of time was assigned to the extraction and purification process in a LC-MS/MS development [32]. The one-step protein precipitation used in this method was a simple, efficient, and economical way which has been widely reported by some researchers [4, 30, 33], while solid phase extraction and liquid-liquid extraction were more time-consuming and wasteful. To further improve the detection sensitivity, we diluted the supernatant after the protein precipitation with different proportion of water-methanol mixture.…”
Section: Resultsmentioning
confidence: 99%